INFLIXIMAB: HAVE ALL QUESTIONS BEEN ANSWERED FOR 10 YEARS? - R M Balabanova; R M Balabanova (Современная ревматология)
The paper provides evidence for the clinical efficacy of infliximab, its effect on the extra-articular manifestations of rheumatoid arthritis-vasculitis, rheumatoid nodules, and cardiovascular pathology. It discusses reasons for the lower effect of therapy and the possibilities of its correction, by increasing the dose of the agent or reducing an infusion interval.